2018
DOI: 10.4269/ajtmh.18-0107
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Use of Antimalarial Medications and Health among U.S. Veterans of the Wars in Iraq and Afghanistan

Abstract: Mefloquine (Lariam; Roche Holding AG, Basel, Switzerland) has been linked to acute neuropsychiatric side effects. This is a concern for U.S. veterans who may have used mefloquine during recent Southwest Asia deployments. Using data from the , a population-based study of U.S. veterans who served between 2001 and 2008, we investigated associations between self-reported use of antimalarial medications and overall physical and mental health (MH) using the twelve-item short form, and with other MH outcomes using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…In summary, we believe Dr. Nevin’s comments 1 on our article 2 are unfounded. The strengths and limitations of our study are noted in the Discussion section.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…In summary, we believe Dr. Nevin’s comments 1 on our article 2 are unfounded. The strengths and limitations of our study are noted in the Discussion section.…”
mentioning
confidence: 81%
“…In a letter to the editor 1 commenting on our article 2 on the association between antimalarial medications (including mefloquine) and health outcomes in veterans, three concerns with our analyses were presented. We disagree with the premise that the stated concerns diminish our findings as they are largely theoretical and lack empirical support.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…I read with interest the article by Schneiderman et al, 1 which examined associations between self-reported mefloquine exposure and recent mental health symptoms among U.S. veterans enrolled in a population-based cohort study. Although the authors’ findings in unadjusted analysis reveal an increased risk that deployed veterans will screen positive for anxiety, depression, and posttraumatic stress disorder (PTSD)–like symptoms with mefloquine exposure, I am concerned that the magnitude of this observed association reflects the influence of information bias, specifically differential misclassification of a more appropriate exposure of interest.…”
mentioning
confidence: 99%